Anxiety and curiosity in hierarchical models of neural emotion processing—A mini review - Hilmerich, Christin; Hofmann, Markus J.; Briesemeister, Benny B. (Frontiers in Human Neuroscience, 2024)
Traditionally, two fundamentally different theoretical approaches have been used in emotion research to model (human) emotions: discrete emotion theories and dimensional approaches. More recent neurophysiological models like the hierarchical emotion theory suggest that both should be integrated. The aim of this review is to provide neurocognitive evidence for this perspective with a particular focus on experimental studies manipulating anxiety and/or curiosity. We searched for evidence that the neuronal correlates of discrete and dimensional emotional systems are tightly connected. Our review suggests that the ACC (anterior cingulate cortex) responds to both, anxiety, and curiosity. While amygdala activation has been primarily observed for anxiety, at least the NAcc (nucleus accumbens) responds to both, anxiety and curiosity. When these two areas closely collaborate, as indicated by strong connectivity, this may indicate emotion regulation, particularly when the situation is not predictable.